2017
DOI: 10.1515/cerce-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Yield Potentiality of Maize as Relay Crop with T. Aman Rice under Different Agronomic Management

Abstract: The experiment was conducted at the Regional Agricultural Research Station, BARI, Ishwardi, Pabna, Bangladesh, during 2013-2014 and 2014-2015 to introduce maize as relay crop with T. Aman rice under different agronomic practices for determine the production potentials. The experiment was design split plot with three replications. The agronomic management practices included four plant spacing viz. S1=75 cm×20 cm (66666 plants/ha), S2=60 cm×20 cm (83333 plants/ha), S3=50 cm×20 cm (100000 plants/ha) and S4=40 cm×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The increase in dry matter production and the capture of solar radiation inside the canopy is closely associated with the rising LAI. Therefore, a decline in LAI is mirrored by a reduction in dry matter production 57 . In a similar vein, Dwyer and Stewart 58 found that crop light interception is significantly influenced by leaf area, which in turn has a significant impact on crop productivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in dry matter production and the capture of solar radiation inside the canopy is closely associated with the rising LAI. Therefore, a decline in LAI is mirrored by a reduction in dry matter production 57 . In a similar vein, Dwyer and Stewart 58 found that crop light interception is significantly influenced by leaf area, which in turn has a significant impact on crop productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The halt of vegetative development, the loss and senescence of leaves, and the reduction in LAI at later growth stages are the causes of the CGR decline after 55 DAS. These factors may have also decreased the photosynthetic efficiency and, eventually, the dry matter accumulation rate 57 . The CGR under KL 2 was reduced significantly compared to KL 1 in mung bean genotypes at different stages of life span.…”
Section: Resultsmentioning
confidence: 99%
“…LAI reached to a maximum level at 50% flowering stage then decreased at a later growth stage (YCS and RiS), because of leaves shading. Hence, dry matter produced decreases with decreasing of LAI (Islam et al, 2017) and therefore has a large influence on crop yield (Dwyer and Stewart, 1986). Srivastava et al (2005) also reported that LAI was positively correlated with accumulated GDD in mustard.…”
Section: Leaf Area Index (Lai)mentioning
confidence: 98%
“…The dry weight per unit of area was higher with 'BARI Sharisha-16' indicating the favorable response of biomass production. Islam et al (2017) reported that dry matter production by the plants depends on the amount of light energy interception by the leaves and its efficiency of conversion into chemical energy. Better dry matter production and its proper translocation into reproductive organ are the prime requisites of higher productivity of a crop (Ahmed et.al, 2010).…”
Section: Dry Matter Partitioning At Different Growth Phases Of Mustardmentioning
confidence: 99%
“…At present major maize based cropping pattern viz. potato intercropped with maize (Ifenkwe and Odurukwe, 1990;Begum et al, 2016), maize-vegetables and spices (Nazrul, 2018) intercropping, potato-maize-T. aman rice, maize-relay with T. aman rice (Islam et al, 2017), maize-pre monsoon aus rice-T.aman rice, maize-bushbean (Islam, 2002) are being practiced by the farmers. However, maize-fallow-T. aman rice cropping patterns are being disseminated day by day in other maize growing areas of Bangladesh (Yusuf et.…”
Section: Introductionmentioning
confidence: 99%